Cyber Mercenaries: A New Threat to National Security. - de Arimatéia da Cruz, José (International Social Science Review, 2020)
The article focuses on cyberattacks as a new threat to national security. Topics discussed include views of Tim Maurer, co-director of the Cyber Policy Initiative, on aspect of cyberspace, the book Cyber Mercenaries: The State, Hackers, and Power by Maurer and views of Robert Knake, the Whitney Shepardson Senior Fellow at the Council on Foreign Relations (CFR), on offensive cyber operations.